Dye exchanged zeolitic markers

The dye-exchanged zeolite markers prepared by cation exchange reaction are combined into the zeolite pores, solving the problem of insufficient stability of the labeled materials in the prior art under high temperature or solvents, and achieving higher stability and effective detection.

CN119630731AActive Publication Date: 2025-03-14SAES GETTERS SPA

Patent Information

Application Number
CN202380056147.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-29
Filing Date
2023-07-28
Publication Date
2025-03-14
Estimated Expiration
2043-07-28

AI Technical Summary

Technical Problem

In the prior art, the labeling material used to detect a specific substance is easily released and decomposed in high temperatures or in the presence of a solvent, resulting in insufficient stability.

Method used

The dye-exchanged zeolite marker prepared by a cation exchange reaction between the positive ions of the zeolite and the positive ions of the dye organic molecules, the dye is effectively bound to the zeolite pores, improving the stability of the marker.

Benefits of technology

Markers that do not release or decompose in the presence of high temperatures or solvents are achieved, stability is significantly improved, and effective detection can be achieved with a lower dye/zeolite ratio.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630731A_ABST
    Figure CN119630731A_ABST
Patent Text Reader

Abstract

A dye exchanged zeolite marker wherein the zeolite is characterized by a pore size from # imgabs 0 # to # imgabs 1 # and the dye is an organic cationic molecule, characterized in that the amount of the dye is from 0.05 wt% to 1 wt% relative to the weight of the zeolite; an optically active composition comprising a dye exchanged zeolitic marker dispersed in a polymer matrix; and their use as detectable markers.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] The present invention relates to dye-exchanged zeolite labels and optically active compositions comprising said labels dispersed in a polymer matrix.

[0002] Many patent publications (e.g., EP1409997, EP1356478, WO2011045572, WO2021113377 or US20100003762) relate to the preparation of marking materials for a wide range of possible applications (e.g., for anti-counterfeiting purposes, for inventory control or warranty purposes, for detecting the presence of a specific substance in a specific medium, or as a package solution). Known means for detecting specific substances are represented by the use of colorimetric indicators, which rely on the optical properties of reactive dyes or inks under specific conditions. In particular, these dyes can exist in at least two different chemical states, wherein each form of dye absorbs light within a specific wavelength range. When such a reactive dye existing in a first form is exposed to a given substance, it reacts with the substance by a reversible chemical reaction, thereby being converted into a second form of dye. Because the second form of dye absorbs light under different wavelengths, chemical reaction provides a visible and therefore detectable color change.

[0003] The integration of the molecule into the desired substrate (which also includes the possibility of using zeolites) is usually achieved by an impregnation method as disclosed in WO2011045572 or by a post-treatment method as reported in US11027241. In addition, CN110903826 discloses the use of fluorescent molecules such as rhodamine integrated on the surface of a metal organic framework (Metal-Organic Framework, MOF) type structure using diffusion impregnation technology. At the same time, WO2021113377 describes antimicrobial zeolite nanoparticles, which, in addition to metal substances, may also contain optical tracers (e.g., fluorophores) that are non-covalently or covalently bound to the surface of the zeolite but not in the pores of the nanoparticles.

[0004] The main drawback of such a process is related to the limited stability of the final system, which tends to decompose easily releasing the dye molecules when exposed to thermal treatments, for example under extrusion processing in the case of thermoplastic matrices, or in the presence of water or other solvents.

[0005] Another possible method is based on the use of pigments, as reported in WO2005052069, in which the pigment composition is achieved by substitution reaction with one or more cationic dye groups in the presence of a suspension of zeolite pigments. However, one of the negative consequences of using both organic and inorganic pigments as disclosed in WO2005052069 is related to the large amount of dye relative to the amount of zeolite and the resulting high dye / zeolite ratio required to achieve the coloring purpose.

[0006] Therefore, there remains a need to develop new chemical indicators, and in particular markers, to provide simple, reliable and cost-effective detection means that exhibit improved stability relative to those known in the art, particularly when exposed to heat or in contact with solvents. In addition, there is a need to develop new optically active compositions incorporating such markers that can be prepared and processed by known polymer processing techniques while maintaining the efficacy and stability of the new indicators. Summary of the invention

[0007] The present invention overcomes the above-mentioned disadvantages of the prior art by realizing a dye-exchanged zeolite marker prepared by a cation exchange reaction between the positive ions of the zeolite and the positive ions of the dye organic molecule.

[0008] In the context of the present disclosure, the expression "dye-exchanged zeolite marker" should be interpreted as known in the art and in particular as meaning a marker or indicator based on zeolite and obtainable by a cation exchange reaction between a cationic dye and a zeolite. The short form "marker" can be used interchangeably with "dye-exchanged zeolite marker".

[0009] More specifically, in order to provide a marker substance that can overcome the prior art problems associated with the low stability disclosed above, the inventors of the present invention unexpectedly found that when a cation exchange reaction occurs between the dye and the zeolite, the dye is more effectively bound to the zeolite, in particular to the pores of the zeolite, and therefore will not be released or decomposed when in contact with a solvent or under high temperature conditions, that is, it is more stable than those known in the art.

[0010] Therefore, the present invention relates to a dye-exchanged zeolite marker comprising a zeolite and a dye organic molecule, said marker being obtainable by a cation exchange reaction between at least one positive ion of the zeolite and at least one positive ion of the dye organic molecule.

[0011] Furthermore, it has been demonstrated that by using a reduced amount of dye molecules relative to the zeolite, it is still possible to measure the detectable properties of the obtained marker without changing the surface properties of the zeolite and its adaptability to different applications. Therefore, the present invention also relates to a dye-exchanged zeolite marker comprising a zeolite and a dye organic molecule, wherein advantageously, the weight ratio between the dye and the zeolite is between 0.05% and 1% by weight, preferably between 0.1% and 0.5% by weight, relative to the weight of the zeolite. In other words, contrary to what is disclosed in the prior art, the marker of the present invention does not require a high dye / zeolite ratio to achieve coloring purposes.

[0012] As will be apparent from the experimental section of this disclosure, the measurement of zeolite pores can play a critical role in the preparation of the dye-swapped zeolite markers of the present invention, at least in terms of process yield. It has been found that the pore size is to Zeolites Dye-exchanged zeolites are particularly advantageous.

[0013] The present invention also relates to optically active compositions comprising the dye-exchanged zeolite markers disclosed herein and a polymer matrix, preferably wherein the marker is dispersed within said polymer matrix.

[0014] Furthermore, the present invention relates to the use of the dye-swapped zeolite or composition disclosed herein as a detectable marker, and to a detectable article comprising, embedded or coated (at least partially) with a dye-swapped zeolite or composition according to the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1: is a graph representing the thermogravimetric analysis combined with mass spectrometry (TG-MS) to evaluate the organic vapor release of samples C2 and S2 during the processing simulation. During the temperature increase to 250°C, for sample C2, it is clearly determined that some organics are released due to the onset of decomposition, while for sample S2, the absence of any organic release (always at zero level) confirms that no decomposition process is induced in this sample due to the stability of the dye-zeolite combination. DETAILED DESCRIPTION

[0016] As expected above, the inventors of the present invention found after extensive experiments that dye-exchanged zeolite markers obtained by cation exchange reaction between zeolite and dye are more stable than other zeolite-based markers known in the art in which the dye is merely adsorbed onto zeolite.

[0017] The present invention therefore relates to a dye-exchanged zeolite marker comprising a zeolite and an organic cationic dye, said marker being obtainable by a cation exchange reaction between at least one positive ion of the zeolite and at least one positive ion of the organic cationic dye.

[0018] As will be apparent from the experimental section of this disclosure, the inventors have found that pore sizes of to Zeolites of are particularly advantageous because they allow the dye to bind to the zeolite more effectively, as well as allowing for better process yields. Surface area and porosity analysis was performed using a Micromeritics BET instrument. Prior to analysis, the samples were pretreated by degassing at 180°C in a turbo vacuum, which allowed the removal of physically bound impurities from the analyzed material. The analysis was then continued using CO2 for LTA (at -20°C) or using Ar for other zeolites (at -186°C). The Dubinin Astakhov model was used to calculate the micropore surface area, while the Saito Foley model or the NLDFT model was used to calculate the pore size.

[0019] Another important feature of the markers obtainable according to the invention is that they allow effective detection despite rather low values ​​of the dye / zeolite weight ratio (see samples S1 to S4, Table 1). Surprisingly, the markers allow effective detection without changing the surface properties of the zeolite even at a weight ratio between the dye and the zeolite of 0.05% to 1% by weight, preferably 0.1% to 0.5% by weight (inclusive values), relative to the weight of the zeolite.

[0020] Thus, the present invention relates to a dye-exchanged zeolite marker comprising a zeolite and a dye, wherein:

[0021] - Zeolites are characterized by pore sizes of to

[0022] - the dye is an organic cationic molecule, and

[0023] - The amount of dye is from 0.05% to 1% by weight relative to the weight of the zeolite.

[0024] Zeolites suitable for the purpose of the present invention are the zeolites generally known in the art, provided that they have a pore size of to Preferably, the zeolite is a faujasite-type zeolite (FAU) or a mordenite (MOR).

[0025] The dye is a colorimetric dye commonly known in the art, preferably an organic cationic dye. Preferably, the dye is rhodamine or a derivative thereof, more preferably, the dye is selected from the following: rhodamine B, tetramethylrhodamine isothiocyanate-dextran, rhodamine 6G, rhodamine B isothiocyanate, rhodamine perchlorate 19 and other rhodamine derivatives.

[0026] According to any embodiment of the present invention, the zeolite is composed of X 90Value (where X 90 It means that 90% of the particles in the sample, based on volume, are contained in a spherical diameter within a given range) and the average particle size characterized by the powder is 0.5 μm to 50 μm, preferably 0.5 μm to 20 μm.

[0027] One of the further advantages associated with said markers is related to the possibility of utilizing the zeolite surface for further functionalization and activation, since the dye is effectively bound to the interior of the zeolite.

[0028] In fact, in a preferred embodiment of the present invention, the zeolite surface of the marker is modified by alkoxysilanes such as (3-aminopropyl)trimethoxysilane, (3-aminopropyl)triethoxysilane, N-trimethoxysilylpropyl-N,N,N-trimethylammonium chloride, octadecyldimethyl(3-trimethoxysilylpropyl)ammonium chloride, tetradecyldimethyl(3-trimethoxysilylpropyl)ammonium chloride, n,n-didecyl-N-methyl-N-(3-trimethoxysilylpropyl)ammonium chloride, s-(trimethoxysilylpropyl)isothiourea Chloride, 3-(trihydroxysilyl)propyldimethyloctadecyl ammonium chloride, silsesquioxanes 3-(dimethyloctadecylammonio)propyl, hydroxy-terminated, chloride and (3-glycidoxypropyl)trimethoxysilane. The modification is carried out with alkoxysilanes by hydrolysis and condensation. Preferably, the alkoxysilane derivative or alkoxysilane moiety is present in an amount of 1 wt % to 40 wt % relative to the weight of the zeolite. The silane moiety can then be utilized due to its inherent properties or used as a linking group for further reactions or polymerization steps.

[0029] The dye-exchanged zeolite markers according to any embodiment disclosed herein may also be dispersed in a polymer matrix to obtain an optically active composition.

[0030] Therefore, the present invention also relates to a composition comprising a dye-exchanged zeolite marker according to any embodiment disclosed herein and a polymer or polymer matrix. The polymer matrix should be characterized by having no excitation characteristics and emission characteristics (peaks and / or more complex spectral characteristics resulting from a general increase in absorption and / or emission) at levels that may interfere with the marker excitation or emission. In detail, since the dye excitation peaks and emission peaks of rhodamine or rhodamine derivatives are concentrated at 560nm and 580nm, respectively, and considering the buffer spectral region determined within ±100nm, a suitable polymer matrix is ​​characterized by having no excitation characteristics and emission characteristics within the range of 460nm to 680nm.

[0031] In a preferred embodiment, the polymer matrix is ​​selected from the following: polyethylene (PE); polypropylene (PP); polystyrene (PS); polyethylene terephthalate (PET); acrylonitrile butadiene styrene (ABS) and its copolymers and functionalized polymers; acrylic resins; acrylic-styrene, vinyl and alkyl copolymers; urethane-acrylic resins; aliphatic-urethanes; urethanes; polyurethanes; epoxy resins; siloxanes and polysiloxanes; phenolic resins; poly[ethylene-co-(vinyl alcohol)] (EVOH); poly(vinyl alcohol) (PVAL); poly(lactic acid-co-glycolic acid) (PLGA); polyethylene glycol (PEG); poly(vinyl acetate) (PVAC); aqueous or water-reducible latex; polylactic acid (PLA); aliphatic / aromatic copolyesters, preferably polybutylene adipate terephthalate (PBAT) and poly(butylene sebacate-co-terephthalate) (PBSeT), poly(butylene succinate-co-terephthalate) (PBST); aliphatic copolyesters from 1,4-butanediol and carboxylic acids, preferably poly(butylene succinate) (PBS) and polybutylene succinate adipate (PBSA); polyhydroxyalkanoates (PHA), preferably polyhydroxybutyrate (PHB), poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV), polyhydroxybutyrate-hexanoate (PHBH); natural polymers, in particular polysaccharide polymers, such as chitosan, sodium alginate and starch or modified starch; and mixtures thereof. Preferred examples of polymer blends are blends of polylactic acid (PLA) and polyhydroxybutyrate / polyhydroxyvalerate (PHBV), or blends of polyvinyl alcohol (PVOH) and hydroxypropylated starch ether (STARCH).

[0032] In the active composition obtained, the dye-exchanged zeolite marker is preferably present in an amount ranging from 0.1% to 10% by weight relative to the weight of the polymer matrix.

[0033] In another embodiment, one or more additional components (e.g. fillers) are added to the composition, preferably in an amount of 0.1% to 20% by weight relative to the polymer matrix. The additional components may be selected, for example, from hydrotalcite, zirconium phosphate, porphyrin, graphene and other two-dimensional crystals, zeolites, halloysite, graphene oxide, metal organic frameworks (MOFs), organic beads, cellulose and antioxidant capsules, self-assembling proteins, ester-terminated polyamides, tertiary amide-terminated polyamides, polyether polyamides, polyalkylene oxide-terminated polyamides, and mixtures thereof.

[0034] As will be apparent from the following non-limiting examples, the dye-exchanged zeolites of the present invention and polymer compositions comprising the same are demonstrated to possess effective optical activity.

[0035] Therefore, the present invention also relates to the use of the dye-exchanged zeolite or a polymer composition comprising the same as a detectable marker.

[0036] As will be apparent to one skilled in the art, the dye-exchanged zeolites or polymer compositions of the present invention may be embedded or coated onto articles (eg, packaging, fabrics, general plastic articles, etc.) thereby rendering the article itself, or at least a portion thereof, detectable.

[0037] Therefore, the present invention also relates to an article or product at least partially comprising, embedded with or coated with a dye-exchanged zeolite or polymer composition according to any embodiment disclosed herein, preferably selected from packaging, textiles, clothing, devices (e.g. medical devices), optical labels, marking components, anti-counterfeiting elements.

[0038] In view of the above, the composition comprising the dye-exchanged zeolite according to any embodiment of the present invention may be processed into the form of a coating, film, paint, frame, three-dimensional element, pellet or sheet, or generally into any other form suitable for the intended purpose.

[0039] The label can be used as such or included in a polymer matrix as disclosed above to obtain an optically active composition.

[0040] Several methods can be used to prepare polymer / zeolite composites, such as in-situ polymerization, polymer dissolution and mixing, extrusion, melt blending or other shaping processes (eg, injection, transfer, compression, foaming, thermoforming, film blowing).

[0041] As will be apparent from the following experimental section, the present invention also relates to a process for preparing a polymer composition comprising a dye-exchanged zeolite marker according to any embodiment disclosed herein by in situ polymerization, polymer dissolution and mixing, or melt blending, and to compositions obtainable therewith.

[0042] Experimental Section

[0043] In the following, the invention will be described in more detail with reference to the following non-limiting examples.The appended claims cover modifications or variations of the embodiments illustrated herein that are obvious to an expert in the field.

[0044] Preparation of rhodamine-exchanged zeolite markers (samples S1 to S6 and counterexample C1)

[0045] Rhodamine B (RhB) or RhB-dextran (both from SigmaAldrich) in an amount of 0.05 g to 1.25 g was dissolved in 100 mL of distilled water. Then 5 g of zeolite was added to the mixture, and the pH of the mixture was adjusted to 6 using HCl (1 M) solution. The mixture was stirred for 24 hours at room temperature using a laboratory magnetic stirrer in the dark. The obtained complex was then purified by filtration. Purification included washing the powder thoroughly with distilled water until the collected filtrate looked completely transparent. The obtained rhodamine exchanged complex was dried overnight in an oven at 80 ° C.

[0046] Table 1

[0047]

[0048] The ion exchange reaction (C1) using 0.25 g of RhB with LTA zeolite resulted in a very low content of Rhodamine B in the LTA zeolite (0.02 wt%), making this sample unsuitable for use as a marker.

[0049] Preparation of Counterexample C2

[0050] An amount of 0.25 g of Rhodamine B (RhB) was mechanically mixed with 5 g of zeolite, ensuring efficient dispersion of the different materials in powder form. The obtained mixture was dried in an oven at 80° C. overnight.

[0051] Preparation of Counterexample C3

[0052] 0.25 g of 9-(diethylamino)-5H-benzo[a]phen Oxazine-5-one (surrogate marker NR) was dissolved in 100 mL of dimethyl sulfoxide. Then 5 g of zeolite was added to the mixture. The mixture was stirred for 24 hours in the dark using a laboratory magnetic stirrer at room temperature. The obtained complex was then purified by filtration. Purification included washing the powder thoroughly with distilled water until the collected filtrate looked completely transparent. The exchanged complex obtained was dried overnight in an oven at 80 ° C.

[0053] Preparation of Counterexample C4

[0054] 0.25 g of 5 (6) -fluorescein isothiocyanate (surrogate marker FITC) was dissolved in 100 mL of distilled water. 5 g of zeolite was then added to the mixture. The mixture was stirred for 24 hours at room temperature using a laboratory magnetic stirrer in the dark. The obtained complex was then purified by filtration. Purification included washing the powder thoroughly with distilled water until the collected filtrate looked completely transparent. The exchanged complex obtained was dried overnight in an oven at 80 ° C.

[0055] Preparation of Counterexample C5

[0056] Prepare 3-aminopropyl) triethoxysilane-rhodamine (APTES-RhB) molecules and then attach them to the zeolite surface. For its synthesis, follow the scheme described in T.Nedelcev et al. / Dyes and Pigments 76 (2008) 550e556. In brief, Rhodamine B (0.002mol, 0.96g) is dissolved in chloroform (30ml). The solution is stirred and heated to the boiling point of chloroform (61.2°C). Then APTES (from ABCR) (0.002mol, 0.465ml) is added dropwise to the Rhodamine B solution under stirring. The reaction is stopped after 30 minutes, and chloroform is then removed from the reaction mixture using a rotary evaporator. The remaining material (silylated rhodamine, about 1.3g) is dried in an oven at 60°C.

[0057] Release tests on samples S1 to S6 and counterexamples C1 to C4

[0058] In order to verify that in the zeolite marker of dye exchange, dye is effectively bonded to zeolite, and therefore will not release when contacting with solvent or being subjected to higher temperature, marker dispersion can be directly studied.Selected samples (S1 to S6) or counterexamples (C1 to C4) of the amount of 22.4mg are dispersed in 20g solvent.The sample is stirred vigorously at room temperature (RT), and the subsequent 24 hours of its sedimentation are made.As follows, the outward appearance of supernatant is analyzed by simple naked eye observation, and compared with the reference colored sample (R1) obtained by dissolving 1.12mg (2,34E-06mol) RhB powder in 20g solvent.The solvent list adopted includes distilled water, acetone, dimethyl sulfoxide, tetrahydrofuran, chloroform and dichloromethane (DCM).As reported in Table 2, for all solvents adopted, the completely transparent dispersion has confirmed the absence of the dye released.

[0059] As an additional test, the prepared sample dispersion was stirred vigorously for 10 minutes at 50°C and then allowed to settle for 24 hours. As follows, also in this case, the appearance of the supernatant of the sample was analyzed by simple visual observation and compared with the reference colored dye sample. The completely transparent dispersion confirmed the absence of the released dye, and the absence of the spectrophotometric signal associated with the dye confirmed the absence of its release. As reported in Table 2, the stability results observed for the room temperature samples were confirmed after the heat treatment.

[0060] The dispersions prepared as reported above were further analyzed by UV-Vis spectrophotometry. Calibration curves were determined for each solvent and a detection limit (DL) of 1 ppm was determined. The effects of some parameters such as solvent characteristics, temperature and stirring time were studied. The results are reported in Table 3 and the detection limit for each solvent was determined in the absence of an absorption peak, and the calculated relative error was 15%.

[0061] Table 2. Dissolution of markers of samples in selected solvents (x = dye not released; √ = dye released). Tests were performed at room temperature and after 10 minutes at 50°C; observations were made after 24 hours.

[0062]

[0063]

[0064] Table 3. Dye release of samples in selected solvents.

[0065]

[0066]

[0067] To confirm the increased stability of the markers prepared according to the present invention, samples C2 and S2 were further exposed to a heat treatment simulating polymer processing in a Thermal Gravimetric Mass Spectrometry (TG-MS) instrument (characterized by a rapid temperature increase to 250°C (50°C / min) and a 5-min isothermal) to determine traces of organic matter from the decomposition of Rhodamine B. As reported in Figure 1, when sample C2 was subjected to the above treatment, some organic matter was clearly identified, while for sample S2, the organic matter remained at zero level.

[0068] Contact angle test

[0069] Contact angle measurement is a technique used to determine the wetting characteristics of a liquid drop on a solid surface. The contact angle is the angle formed between the tangent line at the three-phase contact line of the liquid drop and the solid surface.

[0070] Initially, a solid substrate of interest is prepared to measure wetting behavior. In this case, the substrate is a zeolite powder pellet. Then, a small droplet of the liquid under investigation is carefully placed onto the solid surface using a syringe, micropipette, or other precise dispensing method.

[0071] Finally, a high-resolution camera captures an image of the droplet on the solid surface from a suitable angle. Compared to standard protocols, for zeolite pellets, the acquisition must be very fast, in less than 1 second. The acquired image is then processed using specific software to analyze the shape of the droplet and determine the contact angle.

[0072] If water is used as the liquid probe, the sample is labeled as hydrophilic (polar surface, strong interaction with H2O) when the contact angle is <90°, and as hydrophobic when the result is >90°.

[0073] The surface of ordinary zeolites is hydrophilic, but when the powder surface is functionalized with organic molecules, it can become hydrophobic.

[0074] Contact angle analysis was performed on sample S2 and counterexample C5 and the related results reported in Table 4 demonstrate that only according to the procedure of the present invention it is possible to have rhodamine in the pores of the zeolite, whereas following the procedure known in the art the rhodamine is bound on the external surface.

[0075] Thus, in contrast to hydrophobic zeolites such as C5, the zeolites disclosed herein comprising rhodamine in the interior of the pores are more easily integrated into further matrices / compositions and, in addition, are characterized by the possibility of further interactions or functionalizations on the surface.

[0076] Table 4. Contact angle values

[0077] serial number sample <![CDATA[Contact angle H2O (°)]]> S2 FAU5.1_RhB_13 <![CDATA[ 16.5±1.6 <!-- 8 -->]]> C5 FAU5.1_APTES-RhB <![CDATA[ 99.7±3.8 ]]>

[0078] Method for preparing a dye-exchanged zeolite marker dispersed in a polymer matrix to obtain an optically active composition Law.

[0079] Several methods can be used to prepare polymer / zeolite composites, such as in situ polymerization, polymer dissolution and mixing, or melt blending.

[0080] The preparation by in situ polymerization is based on a first step involving the formulation of polymer precursors, followed by the introduction of the dye by using effective techniques to obtain a fine dispersion. After obtaining a uniform dispersion, the liquid formulation is applied to a support, where the polymerization process is promoted by initiator activation. Depending on the initiator characteristics and the formulation chemical composition, different activation fields can be employed. Typical methods are based on thermal processing or UV irradiation.

[0081] The solution mixing method includes four steps: dissolving the polymer matrix in a suitable solvent at room temperature or elevated temperature, dispersing the zeolite in the solvent, mixing the two solutions by mechanical stirring or tip / bath sonication, and finally precipitating or casting the mixture to obtain a membrane after evaporation of the solvent.

[0082] Melt blending is a common technique for making thermoplastic / zeolite composites. It utilizes high temperatures and high shear forces to disperse the zeolite and is compatible with industrial processes. Depending on the desired final form / shape of the composite, bulk materials can be processed by different post-extrusion techniques (e.g., film forming, injection molding, compression molding, melt spinning).

[0083] Different examples of different preparation methods according to the invention are reported below:

[0084] Example Preparation method AC 1 to 5 In-situ polymerization AC 6 to 14 Polymer dissolving and mixing AC 15 to 18 Melt Blending

[0085] Sample AC 1. A film of the active composition was prepared by mixing 1.5 g of polyethylene glycol dimethacrylate (PEGDMA) with 0.07 g of ESACURE ONE (bifunctional oligomeric α-hydroxyketone) from IGM resin as a free radical generating photoinitiator. After the photoinitiator was completely dissolved, 0.015 g of rhodamine-zeolite sample S2 was added to the formulation at room temperature and mechanical mixing was continued for 30 minutes. The obtained formulation was spread on a glass substrate by a spatula at a thickness of 50 microns and was illuminated by using an irradiance of 100 mW / cm 2 UV lamp was focused at 365 nm for 15 seconds (radiation dose was 1.5 J / cm 2 ) to promote the polymerization process. The polymerization process was carried out in a glove box environment under an inert gas flux. A reference PEGDMA (UV-cured) film without a marker was also prepared using the same experimental protocol.

[0086] Sample AC 2. A film of the active composition was prepared by mixing 1.5 grams of polyethylene glycol dimethacrylate with 0.07 grams of azobisisobutyronitrile (AIBN) from Sigma Aldrich as a thermal initiator for generating free radicals. After the initiator was completely dissolved, 0.015 grams of rhodamine-zeolite sample S2 was added to the formulation at room temperature and mechanical mixing was continued for 30 minutes. The obtained formulation was spread on a glass substrate by a spatula with a thickness of 50 microns and the polymerization process was promoted by heating the sample at 80° C. for 30 minutes. The polymerization process was carried out in a glove box environment under an inert gas flux.

[0087] A reference PEGDMA (heat cured) film without labeling was also prepared using the same experimental protocol.

[0088] Sample AC 3. Add 0.9 g Epikote from Hexion TM 862 (bisphenol F resin) with 0.15 g of Epon 8111 (epoxy acrylate resin) from Hexion and 0.38 g of Epikote TMThe film of the active composition was prepared by mixing with 03161 (rubber-modified bisphenol A resin). The obtained preparation was vigorously stirred for 1 hour by mechanical mixing to obtain a uniform solution. Then 0.08 grams of triarylsulfonium hexafluoroantimonate as a cationic initiator was added and dissolved by mechanical stirring for 30 minutes. After the initiator was completely dissolved, 0.015g of rhodamine-zeolite sample S2 was added to the preparation at room temperature and mechanical mixing was continued for another 30 minutes. The obtained preparation was spread on a glass substrate with a thickness of 50 microns by a scraper and an irradiance of 100mW / cm 2 The polymerization process was accelerated by UV treatment (where λ=365 nm) for 120 seconds.

[0089] A reference diglycidyl ether of bisphenol F (DGEBF) based film without marker was also prepared using the same experimental protocol.

[0090] Sample AC 4. Add 1.35 g DOW Sylgard TM The 184A part (polydimethylsiloxane, PDMS) was mixed with 0.15 gram of the 184B part (dimethyl, methyl hydrogen siloxane copolymer) of DOW as a crosslinking agent for 10 minutes to prepare the film of the active composition. Then, at room temperature, 0.015g of rhodamine-zeolite sample S2 was added to the preparation, and mechanical mixing was continued for another 10 minutes. After obtaining uniform dispersion, the degassing process under vacuum was continued for 15 minutes. The preparation obtained was spread on a glass substrate with a thickness of 50 microns by a scraper, and the polymerization process was promoted by heating the sample at 100 ℃ for 30 minutes.

[0091] A reference PDMS membrane without markers was also prepared using the same experimental protocol.

[0092] Sample AC 5. A film of the active composition was prepared by mixing 1.45 g of SunChemical's COMPOST LAM ADH (polyurethane based on aliphatic polyisocyanate, PU) with 0.05 g of an alcohol dehydrogenase catalyst. Then 0.015 g of the rhodamine-zeolite sample S2 was added at room temperature and the dispersion was stirred by mechanical mixing for 15 minutes. The obtained formulation was spread on a glass substrate by a spatula at a thickness of 50 microns and the crosslinking reaction was promoted at room temperature.

[0093] A reference PU film without markers was also prepared using the same experimental protocol.

[0094] Sample AC 6. 1.5 g of LyondellBasell 2420 grade low density polyethylene (LDPE) was dissolved in 8.5 g of toluene at a boiling temperature of 110° C. After the polymer was dissolved, 0.015 g of rhodamine-zeolite sample S2 was added to the polymer solution at room temperature and the dispersion was mixed by bath sonication at room temperature for 30 minutes and vigorously stirred by mechanical mixing for 1 hour.

[0095] The obtained formulation was spread on a Teflon foil with a thickness of 50 microns by doctor blade and the evaporation of the solvent was promoted at 50° C. A composite film containing 1 wt % marker in the polymer matrix was obtained. A reference LDPE film without marker was also prepared using the same experimental protocol.

[0096] Sample AC 7. 1.5 g of Versalis N1910 (ENI) grade atactic polystyrene (PS) was dissolved in 8.5 g of toluene at a boiling temperature of 110°C. After the polymer was dissolved, 0.015 g of rhodamine-zeolite sample S2 was added to the polymer solution at room temperature, and the dispersion was mixed by bath sonication at room temperature for 30 minutes and vigorously stirred by mechanical mixing for 1 hour. The obtained preparation was spread on a Teflon foil with a thickness of 50 microns by a spatula, and the solvent evaporation was promoted at 50°C. A composite film containing 1% by weight of the marker in the polymer matrix was obtained. A reference PS film without marker was also prepared using the same experimental protocol.

[0097] Sample AC 8. 1.0 g of GoodFellow's polylactic acid (PLA) (MFR=8) was dissolved in 9.0 g of chloroform at a boiling temperature of 61°C. After the polymer was dissolved, 0.01 g of rhodamine-zeolite sample S2 was added to the polymer solution at room temperature, and the dispersion was mixed by bath sonication at room temperature for 30 minutes and vigorously stirred by mechanical mixing for 1 hour. The obtained preparation was spread on a Teflon foil with a thickness of 50 microns by a spatula, and the solvent evaporation was promoted at 40°C. A composite film containing 1% by weight of the marker in the polymer matrix was obtained. A reference PLA film without marker was also prepared using the same experimental protocol.

[0098] Sample AC 9. 1.0 g of GoodFellow's polyhydroxybutyrate (PHB) was dissolved in 20.0 g of chloroform at a boiling temperature of 61°C. After the polymer was dissolved, 0.03 g of rhodamine-zeolite sample S2 was added to the polymer solution at room temperature and the dispersion was mixed by bath sonication at room temperature for 30 minutes and vigorously stirred by mechanical mixing for 1 hour. The obtained preparation was spread on a Teflon foil with a thickness of 50 microns by a spatula and the solvent evaporation was promoted at 40°C. A composite film containing 3% by weight of the marker in the polymer matrix was obtained. A reference PHB film without marker was also prepared using the same experimental protocol.

[0099] Sample AC 10. 1.0 g of GoodFellow's polyhydroxybutyrate / polyhydroxyvalerate 2% (PHBV) was dissolved in 20.0 g of chloroform at a boiling temperature of 61°C. After the polymer was dissolved, 0.03 g of rhodamine-zeolite sample S2 was added to the polymer solution at room temperature and the dispersion was mixed by bath sonication at room temperature for 30 minutes and vigorously stirred by mechanical mixing for 1 hour. The obtained preparation was spread on a Teflon foil with a thickness of 50 microns by a spatula and the evaporation of the solvent was promoted at 40°C. A composite film containing 3 wt% of the marker in the polymer matrix was obtained. A reference PHBV film without the marker was also prepared using the same experimental protocol.

[0100] Sample AC 11. 1.0 g of Kuraray AQ-4104 grade polyvinyl alcohol (PVOH) was dissolved in 9.0 g of distilled water at a boiling temperature of 100°C. After the polymer was dissolved, 0.01 g of rhodamine-zeolite sample S2 was added to the polymer solution at room temperature, and the dispersion was mixed by bath sonication at room temperature for 30 minutes and vigorously stirred by mechanical mixing for 1 hour. The obtained preparation was spread on a glass substrate with a thickness of 50 microns by a spatula, and water evaporation was promoted at 50°C. A composite film containing 1% by weight of the marker in the polymer matrix was obtained. A reference PVOH film without the marker was also prepared using the same experimental protocol.

[0101] Sample AC 12. 1.0 g of SOLAM's SOLCOAT P85 grade hydroxypropylated starch ether (STARCH) was dissolved in 9.0 g of distilled water at a boiling temperature of 100° C. After the polymer was dissolved, 0.01 g of rhodamine-zeolite sample S2 was added to the polymer solution at room temperature, and the dispersion was mixed by bath sonication at room temperature for 30 minutes and vigorously stirred for 1 hour by mechanical mixing. The obtained preparation was spread on a glass substrate with a thickness of 50 microns by a spatula, and water evaporation was promoted at 40° C. A composite film containing 1% by weight of the marker in the polymer matrix was obtained. A reference STARCH film without a marker was also prepared using the same experimental protocol.

[0102] Example AC 13 (Blend 1). 0.7 g of GoodFellow's polylactic acid (PLA) (MFR=8) and 0.3 g of GoodFellow's polyhydroxybutyrate / polyhydroxyvalerate 2% (PHBV) were dissolved in 18.0 g of chloroform at a boiling temperature of 61°C. After the polymers were dissolved, 0.05 g of rhodamine-zeolite sample S2 was added to the polymer solution at room temperature and the dispersion was mixed by bath sonication at room temperature for 30 minutes and vigorously stirred by mechanical mixing for 1 hour. After solution casting, a composite membrane containing 3 wt% of marker in the polymer matrix was obtained. A reference PLA / PHBV membrane without marker was also prepared using the same experimental protocol.

[0103] Example AC 14 (Blend 2). Under vigorous stirring, 0.7 g of Kuraray AQ-4104 grade polyvinyl alcohol (PVOH) and 0.3 g of SOLAM's SOLCOAT P85 grade hydroxypropylated starch ether (STARCH) were dissolved in 9.0 g of distilled water at 90°C. After the polymer was completely dissolved, 0.01 g of rhodamine-zeolite sample S2 was added to the polymer solution at room temperature (RT), and the dispersion was mixed by bath sonication at room temperature for 30 minutes and vigorously stirred by mechanical mixing at room temperature for 1 hour. The obtained preparation was spread on a glass substrate with a thickness of 50 microns by a spatula, and water evaporation was promoted at 50°C. A reference PVOH / STARCH film without markers was also prepared using the same experimental protocol.

[0104] Example AC 15. 49 g of low density polyethylene powder ≤ 400 microns purchased from Alfa Aesar was compounded with 1 g of rhodamine-zeolite (sample S2) by melt blending for 5 minutes using a laboratory two-roll open mixer mill (Battaggion). The conditions of the rolling process were: front roll temperature = 130°C; back roll temperature = 80°C; rolling speed = 33 rpm. The resulting composite was compression molded using a laboratory press (Gibitre Instruments) at P = 230 bar and T = 175°C for 5 minutes to obtain a sheet with 2 wt% marker (thickness ≈ 200 μm). A reference polyethylene sheet without marker was also produced following the same experimental protocol.

[0105] Example AC 16. 49 g of polylactic acid (NatureWorks 2003D grade) was compounded with 1 g of rhodamine-zeolite (sample S2) by melt blending for 5 minutes using a laboratory double-roll open mixing mill (Battaggion). The conditions of the rolling process were: front roll temperature = 155°C; back roll temperature = 125°C; rolling speed = 33 rpm. The resulting composite was compression molded for 5 minutes using a laboratory press (Gibitre Instruments) at P = 230 bar and T = 190°C to obtain a sheet (thickness ≈ 200 μm) with 2 wt % marker. The same experimental protocol was also followed to produce a reference polylactic acid sheet without marker.

[0106] Example AC 17. 48.5 g of GoodFellow's polyhydroxybutyrate / polyhydroxyvalerate 2% (PHBV) was compounded with 1.5 g of rhodamine-zeolite (sample S2) by melt blending for 5 minutes using a laboratory two-roll open mixing mill (Battaggion). The conditions of the rolling process were: front roll temperature = 170°C; back roll temperature = 145°C; rolling speed = 33 rpm. The resulting composite material was compression molded using a laboratory press (Gibitre Instruments) at P = 230 bar and T = 190°C for 5 minutes to obtain a sheet with 3 wt% marker (thickness ≈ 200 μm). A reference PHBV sheet without marker was also produced following the same experimental protocol.

[0107] Example AC 18

[0108] 98 g of acrylonitrile butadiene styrene ABS (produced by INEOS STYROLUTION) was milled using a laboratory benchtop double roll mill (LabTech Engineering). GP-22 grade) was compounded with 2g of rhodamine-zeolite (sample S5) by melt blending for 5 minutes. The conditions of the rolling process were: front roll temperature = 175°C; back roll temperature = 170°C; rolling speed = 10 rpm. The resulting composite material containing 2 wt% of marker S5 was formed into a sheet (thickness 500 μm). A reference ABS sheet without marker was produced following the same preparation protocol.

[0109] The examples prepared are summarized in Table 4 below:

[0110]

[0111]

[0112] Optical characterization of markers and substrates.

[0113] Device Description. Using Horiba Plus fluorescence spectrophotometer. A continuous light source P focused on the entrance slit of the excitation monochromator is used. o = 150W ozone-free xenon arc lamp. The instrument is based on two Czerny-Turner monochromators that disperse the incident light through their reflection gratings. The spectrum is obtained by rotating the gratings and recording the intensity values ​​at each wavelength. Both the entrance and exit ports of each monochromator include continuously adjustable slits to control the spectral resolution and intensity of the fluorescence signal recorded by the photomultiplier tube. A solid sample holder mounted on an adjustable goniometer is used to test polymer products in the form of films or plates with added markers. A sample setup with a 60° angle between the incident beam and the mirror-reflected beam is used to prevent the excitation beam from entering the emission slit, thus avoiding interference from stray light. Using FluorEssence TM Analysis management software is used to acquire and process data.

[0114] Description of the sample characterization protocol.

[0115] The marker excitation peak and emission peak in the polymer matrix are compared with reference sample (polymer matrix not containing marker) and pure marker excitation peak and emission peak, to detect the dye inside the polymer matrix exists.By considering dye fluorescence, the sample performance is studied as the fluorescence intensity I of the active composition that stands under 540nm and stands under 540nm and does not contain the fluorescence intensity I0 of the pure polymer matrix of dyestuff that excites between the ratio.According to the scheme adopted, when determining that the value of I / I0 ratio is greater than 2, the marker existence is considered to detectable.The recorded values ​​of all test samples have been reported in the following table 5.

[0116] Table 5

[0117]

[0118]

Claims

1. A dye-exchanged zeolite marker comprising a zeolite and a dye, wherein: a) the zeolite is characterized by a pore size of to b) the dye is an organic cationic molecule selected from the following: rhodamine B, tetramethylrhodamine isothiocyanate-dextran, rhodamine 6G, rhodamine B isothiocyanate, rhodamine perchlorate 19 and other rhodamine derivatives, and c) the amount of the dye is 0.05 wt% to 1 wt% relative to the weight of the zeolite.

2. The dye-exchanged zeolite marker according to claim 1, wherein the zeolite is a faujasite-type zeolite (FAU) or a mordenite (MOR).

3. A dye-exchanged zeolite marker according to any one of the preceding claims, wherein the amount of the dye is from 0.1 wt% to 0.5 wt% relative to the weight of the zeolite.

4. A dye-exchanged zeolite marker according to any one of the preceding claims, wherein the zeolite is in the form of X 90 The value characterizes the average particle size in the form of a powder of 0.5 μm to 50 μm.

5. The dye-exchanged zeolite marker of claim 4, wherein the average particle size is characterized by X 90 The value is 0.5μm to 20μm.

6. The dye-exchanged zeolite label according to any one of the preceding claims, wherein the zeolite comprises a surface modified or functionalized with an alkoxysilane derivative.

7. The dye-exchanged zeolite marker of claim 6, wherein the alkoxysilane derivative moiety is present in an amount of 1 wt% to 40 wt% relative to the weight of the zeolite.

8. The dye-exchanged zeolite marker according to any one of the preceding claims, obtainable by a cation exchange reaction between at least one positive ion of the zeolite and at least one positive ion of the dye.

9. A composition comprising a dye-exchanged zeolite marker according to any one of the preceding claims dispersed in a polymer matrix, wherein the polymer matrix is ​​selected from polyethylene (PE); polypropylene (PP); polystyrene (PS); polyethylene terephthalate (PET); acrylonitrile butadiene styrene (ABS) and its copolymers and functionalized polymers; acrylic resins; acrylic-styrene; acrylic-vinyl and alkyl copolymers; urethane-acrylic resins; aliphatic-urethanes; urethanes; polyurethanes; epoxy resins; siloxanes and polysiloxanes; phenolic resins; poly[ethylene-co-(vinyl alcohol)] (EVOH); poly(vinyl alcohol) (PVAL); poly(lactic-co-glycolic acid) (PLGA); polyethylene glycol (PEG); poly(vinyl acetate) (PVAC); aqueous or water-dilutable latexes; polylactic acid (PLA); aliphatic or aromatic copolyesters, Preferred are polybutylene adipate terephthalate (PBAT) and poly(butylene sebacate-co-terephthalate) (PBSeT); poly(butylene succinate-co-butylene terephthalate) (PBST); aliphatic copolyesters from 1,4-butanediol and carboxylic acids, preferably poly(butylene succinate) (PBS) and polybutylene succinate adipate (PBSA); polyhydroxyalkanoates, preferably polyhydroxyalkanoates (PHA), Polyhydroxybutyrate (PHB), poly (hydroxybutyrate-co-hydroxyvalerate) (PHBV), polyhydroxybutyrate-hexanoate (PHBH); natural polymers, preferably polysaccharide polymers such as chitosan, sodium alginate and starch or modified starch; and mixtures thereof, preferably a blend of polylactic acid (PLA) and polyhydroxybutyrate / polyhydroxyvalerate (PHBV), or a blend of polyvinyl alcohol (PVOH) and hydroxypropylated starch ether (STARCH).

10. The composition of claim 9, wherein the dye-exchanged zeolite marker is present in an amount of 0.1% to 10% by weight relative to the polymer matrix.

11. The composition according to claim 9 or 10, further comprising a filler in an amount of 0.1 to 20% by weight relative to the polymer matrix.

12. The composition according to claim 11, wherein the filler is selected from the group consisting of hydrotalcites, zirconium phosphates, porphyrins, graphene and other two-dimensional crystals, zeolites, halloysites, graphene oxides, metal organic frameworks (MOFs), organic beads, cellulose and antioxidant capsules, self-assembled proteins, ester-terminated polyamides, tertiary amide-terminated polyamides, polyether polyamides, polyalkyleneoxy-terminated polyamides, and mixtures thereof.

13. The composition according to claims 9 to 12, wherein the polymer matrix is ​​processed into the form of a coating, a film, a paint, a frame, a three-dimensional element, a pellet or a sheet.

14. Use of a dye-exchanged zeolite according to any one of claims 1 to 8 or a composition according to any one of claims 9 to 13 as a detectable label.

Citation Information

Patent Citations

  • Tagging materials for polymers, methods, and articles made thereby

    EP1409997A1

  • Method of post-treating zeolite membranes by using dye molecules

    US11027241B2

  • Permanent chemical marker and identification of information in polymers

    US20100003762A1

  • Hybridised pigment

    WO2005052069A2

  • Intelligent pigments and plastics

    WO2011045572A1

Cited By

  • Rapid detection method for zeolite loading capacity and uniformity in zeolite composite material

    CN120721699A